2010
DOI: 10.1007/s11434-009-0724-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in the male-specific SRY gene of Lepus yarkandensis

Abstract: Lepus yarkandensis, an endemic hare species in the Tarim Basin of China, has been suffering from habitat fragmentation due to desert expansion. To evaluate the effect of habitat fragmentation on its genetic diversity, the genetic diversity based on male-specific SRY gene marker is examined. A relatively low level of SRY genetic diversity is found compared to previous studies with mtDNA data, possibly due to the low SRY mutation rate and positive selection. Furthermore, one haplotype exists in eight populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
5
1
Order By: Relevance
“…We ran models with 10 cross-validated replicates by randomly assigning the presence records to training and test datasets (90 and 10%, respectively). We assessed the performance of the models by calculating classification errors using the area under the receiver operating characteristic curve (AUC), sensitivity, specificity, and true skill statistic (TSS = sensitivity + specificity - 1) for each of the 12 models that were cross-validated against the training dataset [130133] [29, 62–64]. We used 75% of the data to calibrate the models and 25% to calculate performance efficiency.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We ran models with 10 cross-validated replicates by randomly assigning the presence records to training and test datasets (90 and 10%, respectively). We assessed the performance of the models by calculating classification errors using the area under the receiver operating characteristic curve (AUC), sensitivity, specificity, and true skill statistic (TSS = sensitivity + specificity - 1) for each of the 12 models that were cross-validated against the training dataset [130133] [29, 62–64]. We used 75% of the data to calibrate the models and 25% to calculate performance efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…The previous habitats of the Yarkand hare may have been more continuous than their current habitat [61]. The previous research on Yarkand hare revealed that desert features, regional aridification, broad rivers [62, 63], and habitat fragmentation of the desert landscape [61] have all been identified as major factors that influence the genetic structure and act as barriers to the dispersal of the species. There was possibly extensive gene flow among populations during the ancient geological period [61].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of Na + is higher and Ca 2+ is lower in blood of L. yarkandensis when compared to that of O. cuniculus , suggesting a strong adjusting ability of L. yarkandensis in maintaining the body water (Gao et al, 1998). In recent years, several researchers have investigated genetic variation, population structure and phylogeography of Yarkand hare (Li et al, 2006), the matrilineal and demographical histories of Tarim Basin’s endemic Yarkand hare (Shan et al, 2011), the bidirectional introgressive hybridization between L. capensis and L. yarkandensis (Wu et al, 2011), for the presence of Leishmania in L. yarkandensis (Gao et al, 2015), and genetic diversity in male-specific SRY gene of L. yarkandensis (Wu et al, 2010). So, the body of L. yarkandensis has specialized height, and it has strong drought tolerance ability when compared with rabbits and other hares (Li, 2011; Hui and Zhao, 2013; Yu and Zhang, 2013; Zhang et al, 2015, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Resolving the phylogenetic relationships between species and different populations within a species is a very important task in evolutionary biology and conservation genetics [ 6 ]. Previous studies exploring the genetic variation and phylogenetic relationships of Yarkand hare populations have focused on mitochondrial DNA (mtDNA) genes [ 8 , 15 , 19 21 ], the male-specific Y-chromosomal sex-determining region ( SRY ) gene [ 21 ], and two nuclear DNA (nDNA) markers, namely, the mechano-growth factor ( MGF ) and spectrin beta non-erythrocytic 1 ( SPTBN1 ) genes [ 8 ]. Phylogenetic analysis of mtDNA sequences showed significant genetic differentiation among most Yarkand hare populations, highlighting low migration levels among populations inhabiting oases isolated by the Taklamakan Desert.…”
Section: Introductionmentioning
confidence: 99%